Analysis of sex-based differences in energy substrate utilization during moderate-intensity aerobic exercise - Cano, A.; Ventura, L.; Martinez, G.; Cugusi, L.; Caria, M.; Deriu, F.; Manca, A. (European Journal of Applied Physiology, 2021)
Purpose To explore sex-based differences in energy substrate utilization during moderate-intensity aerobic exercise; to identify the underpinning candidate physiological mechanisms.